Characterization of the Hepatoprotective Activity of Placenta Cryoextract in Liver Lesions of Various Etiologies - Koshurba, Illia; Chyzh, Mykola; Hladkykh , Fedir (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):292